Efek pemberian Chlorophyllin terhadap kadar nitric oxide dan malondialdehida tikus hiperkolesterolemia - Pontang, Galeh S; Johan, Andrew; Subagio, Hertanto W (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2014)
Background : Endothelial dysfunction is well-known as an early stage of atherosclerosis. Increased oxidative stress inhypercholesterolemia triggers endothelial dysfunction that is characterized by decreased biological availability ofnitric oxide (NO). Experimental studies showed that chlorophyllin had an effective antioxidant activity.Objectives : To determine the effect of chlorophyllin on nitric oxide (NO) and malondialdehyde (MDA) level ofhypercholesterolemic rats.Methods : Post test only randomized control groupusedtwenty four male Sprague Dawley rats were randomly dividedinto four groups: without treatment (technical control/K1), hypercholesterolemic (negative control/K2),hypercholesterolemic with chlorophyllin at dose of 1,8 mg/200 g/d (P1) and hypercholesterolemic with chlorophyllin atdose of 3,34 mg/200g/d (P2). Chlorophyllin was dissolved in water and was given via nasogastric tube for 21 days afterthe rats got hypercholesterolemia. Total cholesterol level of blood was measured by CHOD-PAP method, level of NOplasma was measured by Griess reaction and level of MDA plasma was measured by TBARS method. Hypothesis testwas analyzed by One Way Anova continued by Post hoc LSD test and Kruskall Wallis by significant level of 0,05.Results :NO plasma level was the lowest in group P2 (0.203+0.015 Î¼M) and the highest in the group K2 (0,224Â±0,001Î¼M), but no difference of NO plasma level among groups (p = 0.118). There were differences in MDA plasma levelamong the groups (p = 0.001). P1 and P2 groups had lower MDA plasma level than K2 (2.40+0.11 nmol/ml), indicatedby (1.94 +0.07 nmol/ml, p=0.0001) and (1,37 +0.13 nmol/ml, p=0.0001) respectively, but still higher than K1(0.94+0.05 nmol/ml, p=0.0001).Conclusion : The treatment of chlrophyllin does not have an effect of NO plasma level, but gives an effect of lowerMDA plasma level.